2020
DOI: 10.1016/j.euo.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Cardiovascular Morbidity Following Surgery for Kidney Cancer

Abstract: Background: Despite better renal function following nephron-sparing surgery (NSS) relative to radical nephrectomy (RN), there is no consensus with respect to the long-term sequelae associated with surgery. Objective: To investigate the effect of surgery and the temporal pattern of two different cardiovascular event (CVe) categories after NSS versus RN. Design, setting, and participants: We collected data of 898 patients with cT1-2 N0 M0 renal mass and no history of CVe treated with NSS versus RN. CVe categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 42 publications
0
26
1
Order By: Relevance
“…in addition, recent evidence that NSS might provide better cancer specific mortality may warrant consideration for large renal masses even in an elective setting. 6,16 contrary to previous reports, we found no statistically significant difference regarding clinical tumor size; however, rrN was mostly performed for complex tumors. given the median age of our cohort, one might argue that this could be consequence of the patients age, who are usually managed with rN than PN due to concerns of surgical complications.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…in addition, recent evidence that NSS might provide better cancer specific mortality may warrant consideration for large renal masses even in an elective setting. 6,16 contrary to previous reports, we found no statistically significant difference regarding clinical tumor size; however, rrN was mostly performed for complex tumors. given the median age of our cohort, one might argue that this could be consequence of the patients age, who are usually managed with rN than PN due to concerns of surgical complications.…”
Section: Discussioncontrasting
confidence: 99%
“…3 The widespread adoption of robotic surgery and its well-known technical advantages in terms of visualization and handling of the anatomical structures favored the use of robot-assisted PN (rPN) for large renal masses as well. 4,5 in addition, cardiovascular, 6 and oncological outcomes 7 indicate that PN could also be suitable for elderly patients, who are usually more likely to be elected to rN. 8,9 furthermore, recent evidence suggests that the "oldest old" patients might benefit of PN in terms of surgical functional outcomes, and oncological safety.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that we did not include comorbidities in our preoperative model. Although prior investigators observed an association between AKI and diabetes [18], hypertension [10,19], or smoking status [10], there are reasons to believe that this relationship might be more apparent than real. First, other papers failed to confirm these findings [10,20,21], suggesting that the established association between medical conditions and renal function [5] might not hold true when taking into account a one-time event such as surgical AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al analyzed the SEER-Medicare, and made a conclusion that nearly 20% cardiovascular events rate increased after KC patients treating with radical nephrectomy than nephron-sparing surgery 21 . Umberto et al reported that nephron-sparing surgery showed an independent protective effect on hypertension in KC patients without preoperative cardiovascular disease, but not on other major cardiovascular events 22 . One of the possible pathophysiological mechanisms of this nding is the acute loss of half of nephrons may induce a compensatory function of remaining kidney that increases the arterial blood in ow by activation of the renin-angiotensin-aldosterone system 23,24 .…”
Section: Discussionmentioning
confidence: 99%